COMPARATIVE ANALYSIS OF THE FOAM GLASS GRAVEL TYPES EXPERIMENTALLY PRODUCED BY MICROWAVE IRRADIATION - FELICIA COSMULESCU; LUCIAN PAUNESCU; MARIUS FLORIN DRAGOESCU; SORIN MIRCEA AXINTE (Journal of Engineering Studies and Research)
The paper presents an unconventional technique for manufacturing foam glass gravel. The numerous experimental results obtained by the authors in the last year using various manufacturing recipes common in the world industrial production by conventional techniques were selected and subjected to a qualitative and energy efficiency comparative analysis, aiming to determine the best foam glass gravel manufacturing procedure under the conditions of the use of the microwave energy. The optimum recipe was composed of 83% glass waste, 1 % glycerol, 8 % sodium silicate and 8 % water. The maximum heating temperature reached 823 ºC with a very economical energy consumption of 0.88 kWh/kg. The sample characteristics were apparent density-0.24 g/cm3, porosity-89.1% with pore size between 0.3 - 0.6 mm, thermal conductivity-0.063 W/m·K and compressive strength - 5.9 MPa, almost similar to those industrially obtained.